Young people's transitions in London and temporal orientations of agency (UCL Press, 2014)
This article presents findings from the Changing Youth Labour Markets and Schools to Work Transitions in Modern Britain projects undertaken between 2009 and 2010. The projects examined young people's experiences and perceptions about study, work, and the future while going through transitions. The target group was young people on vocational courses at further education colleges in London aged between 18 and 24. This group is an under-researched cohort, who is neither NEET nor following 'tidy' pathways. We apply the conceptual framework of temporal orientations of agency, originally proposed by Emirbayer and Mische (1998). We discuss the interplay between young people's agency and the contexts in which they live.